The interhemispheric CA1 circuit governs rapid generalisation but not fear memory - Heng Zhou (Nature Portfolio, 2017)
Previous work has documented a slow form of memory generalization although a rapid one is demanded. Here the authors elucidate the role of the interhemispheric CA1-CA1 projection in a form of rapid generalization of contextual fear memory via gradual potentiation of these synapses over 24 h.